Who Cares When Value (Mis)Reporting May Be Found Out? An Acquiring-a-Company Experiment with Value Messages and Information Leaks - Daniela Di Cagno; Werner Güth; Tim Lohse; Francesca Marazzi; Lorenzo Spadoni (Center for Economic Studies and ifo Institute (CESifo), 2023)
We modify the Acquiring-a-Company game to study lying in ultimatum bargaining. Privately informed sellers send messages about the alleged value of their company to potential buyers. Via random information leaks, buyers can learn the true value before proposing a price which the seller finally accepts or not. Two-thirds of all sellers exaggerate the company's value to persuade buyers to offer more, especially when the true value is small. Surprisingly, a higher leak probability does not increase truthtelling. However, it decreases overreporting and increases underreporting. Buyers who found out value misreporting anchor their price proposals on the true value but do not explicitly discriminate against liars. Sellers are fully opportunistic and make their acceptances dependent on the resulting positive payoff. Even if morality concerns do not seem to matter much, probabilistic leaks enhance welfare. That suggests to politically facilitate and encourage e.g. whistle blowing.
Keywords: C78; C91; D83; D91; 330; acquiring-a-company experiments; information leaks; cheap talk (not) lying; ultimatum bargaining